2022
DOI: 10.1097/wnr.0000000000001768
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human erythropoietin protects long-term cultured ageing primary nerve cells by upregulating the PI3K/Akt pathway

Abstract: Objective Previous studies have found that recombinant human erythropoietin (rhEPO) protects long-term cultured ageing primary nerve cells by enhancing the endogenous antioxidant capacity of cells; however, its signalling pathways are not clear. This study aimed to explore the relationship between the rhEPO and PI3K/Akt pathways in the protection of senescent nerve cells at the cellular level. Methods Primary nerve cells were cultured for 22 days to mimic the natural ageing process of nerve cells. rhEPO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Studies have shown that nerve growth factor (NGF) promotes the formation of lamentous pseudopods and branches of axons through the PI3K-Akt signaling pathway [39] . The PI3K-Akt signaling pathway has been shown to be associated with ND [40][41][42] . Considering the regulatory effect of the PI3K-Akt signaling pathway and key targets such as TP53, PI3KCA, PIK3R1, RTK2, and GRB2 on nerve injury and combined with the ndings of previous studies, acrylamide was found to regulate the PI3K-Akt signaling pathway [43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that nerve growth factor (NGF) promotes the formation of lamentous pseudopods and branches of axons through the PI3K-Akt signaling pathway [39] . The PI3K-Akt signaling pathway has been shown to be associated with ND [40][41][42] . Considering the regulatory effect of the PI3K-Akt signaling pathway and key targets such as TP53, PI3KCA, PIK3R1, RTK2, and GRB2 on nerve injury and combined with the ndings of previous studies, acrylamide was found to regulate the PI3K-Akt signaling pathway [43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…It has the same amino acid sequence and similar biological activity as natural EPO, also can cross the blood-brain barrier [10]. Recent years, the protective effect of rhEPO has been proved in many studies in vivo [11] and in vitro [12], however, the role and mechanism of rhEPO on premature immature brain injury induced by HI insult still remain unclear. Thus, in the present study, we investigated the neuroprotective effects of rhEPO as well as its potential mechanism in immature brain injury induced by HI insult.…”
Section: Introductionmentioning
confidence: 99%